PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN MANAJEMEN SEKOLAH SEBAGAI UPAYA MENINGKATKAN MUTU PENDIDIKAN DI SD PLUS ISLAM EXCELLENT BUKITTINGGI - Syafrizal, Fakhri (Graduate Program Magister Manajemen Pendidikan, 2016)
This research aimed at understanding about the role of principal to develop the management to upgrade the educational quality in SD Islam Plus Excellent, Bukittinggi. The educational quality needs the role of principal to make the programs. To get the data, I applied interview and documentation. The results revealed that the principal did make the programs related to management of curriculum, student, teachers and employee, financial, infrastructure, special sevice and relationship to upgrade the educational quality.Â Keywords: Principal, Management, Educational Quality, SD Islam Plus Excellent, Bukittinggi.